Porque é que a Sociedade Pública d’Agricultura e Comércio da Província do Minho não chegou a nascer? - Cardoso, António Barros; Boas, Cláudia Vilas (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The Public Society of Agriculture and Commerce of the Minho Province (Sociedade Pública d’Agricultura e Comércio da Província do Minho), proposed to Queen Maria I of Portugal by the businessmen of Viana in 1784, was never actually created. Despite being inspired by the model idealised at the time of Marquis of Pombal for the wine-growing Douro in 1756, the Board of the General Company for the Agriculture of the Upper-Douro Vineyards (Companhia Geral da Agricultura das Vinhas do Alto-Douro), heard at the request of the Queen on the subject of the creation of such institute, was fiercely opposed to its institution. The present study aims at making known the main reasons for this opposition, highlighting the conflict of interests between both institutes.